2022
DOI: 10.5005/jp-journals-10071-24301
|View full text |Cite
|
Sign up to set email alerts
|

ISCCM Guidelines for Hemodynamic Monitoring in the Critically Ill

Abstract: Hemodynamic assessment along with continuous monitoring and appropriate therapy forms an integral part of management of critically ill patients with acute circulatory failure. In India, the infrastructure in ICUs varies from very basic facilities in smaller towns and semi-urban areas, to world-class, cutting-edge technology in corporate hospitals, in metropolitan cities. Surveys and studies from India suggest a wide variation in clinical practices due to possible lack of awareness, expertise, high costs, and l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 91 publications
0
3
0
Order By: Relevance
“…Fluid responsiveness is defined as an increase in cardiac output (CO) by 10-15% in response to fluid administration [6]. The static measures of preload such as central venous pressure haven't shown consistency in assessing fluid responsiveness and dynamic indices have been proven to be more reliable in predicting fluid responsiveness than the static ones [7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…Fluid responsiveness is defined as an increase in cardiac output (CO) by 10-15% in response to fluid administration [6]. The static measures of preload such as central venous pressure haven't shown consistency in assessing fluid responsiveness and dynamic indices have been proven to be more reliable in predicting fluid responsiveness than the static ones [7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…The interest in CRT was emphasized by the ANDROMEDA-SHOCK study, which demonstrated that, in patients with septic shock, resuscitation aimed at either normalizing CRT or normalizing or decreasing lactate levels during an 8-h intervention period had a similar effect on 28-day mortality [ 3 , 6 ]. CRT is more and more considered as a core monitoring component during resuscitation of septic shock patients [ 7 10 ], particularly in low-resource settings [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Other static markers of cardiac preload are the global end-diastolic volume and the left end-diastolic area/volume, or aortic blood flow, measured by transpulmonary thermodilution, echocardiography, and esophageal Doppler, respectively. However, it has been well-evidenced that dynamic indices are more reliable in predicting fluid responsiveness than static indices [ 2 , 3 ]. This is because the value of these static indices could correspond to a preload responsive or unresponsive state depending on the part of the Frank-Starling curve where fluid resuscitation begins.…”
Section: Introductionmentioning
confidence: 99%